Status Spillovers: The Effect of Status-conferring Prizes on the Allocation of Attention - Reschke, Brian P.; Azoulay, Pierre; Stuart, Toby E. (Administrative Science Quarterly, 2018)
We investigate the effect of a status-enhancing prize on the attention that a recipient’s “neighbors” subsequently receive. Do neighbors—individuals who work in economic, intellectual, or artistic domains that are proximate to prize winners—bask in the reflected glory of the ascendant actor and therefore gain as well? Or does competition for attention ensue, attenuating the recognition neighbors would otherwise have garnered? We study the spillover effects of status shocks using life sciences research articles published from 1984 through 2003. Exploiting expert-assigned article keywords, we identify papers that are topically related to publications of future appointees to the prestigious Howard Hughes Medical Institute (HHMI). In difference-in-difference specifications, we find that these scientific neighbor articles experience substantial declines in citation rates after HHMI appointments are announced. That is, neighboring articles attract less attention when authors of papers near them receive a prestigious prize. This pattern reflects more than the trivial transfer of attention from non-winners to winners: once prizes are announced, actors cede scientific territory to prize winners and pursue other opportunities. These negative spillover effects are moderated or even reversed by scientists’ social connections and by the novelty and stature of scientific domains.